Associations between aflatoxin B1‐albumin adduct levels with metabolic conditions in Guatemala: A cross‐sectional study. Issue 1 (20th January 2022) - Alvarez, Christian S.; Rivera‐Andrade, Alvaro; Kroker‐Lobos, María F.; Florio, Andrea A.; Smith, Joshua W.; Egner, Patricia A.; Freedman, Neal D.; Lazo, Mariana; Guallar, Eliseo; Dean, Michael; Graubard, Barry I.; Ramírez‐Zea, Manuel; et al.
Abstract: Background and Aims: Metabolic conditions such as obesity, type 2 diabetes, metabolic syndrome, and nonalcoholic fatty liver disease (NAFLD) are highly prevalent in Guatemala and increase the risk for a number of disorders, including hepatocellular carcinoma (HCC). Aflatoxin B1 (AFB1 ) levels are also notably elevated in the population and are known to be associated with HCC risk. Whether AFB1 also contributes to the high prevalence of the metabolic disorders has not been previously examined. Therefore, the purpose of this study was to assess the association between AFB1 and the metabolic conditions. Methods: Four‐hundred twenty‐three individuals were included in the study, in which AFB1 ‐albumin adduct levels were measured in sera. Metabolic conditions included diabetes, obesity, central obesity, metabolic syndrome, and NAFLD. Crude and adjusted prevalence odds ratios (PORs) and 95% confidence intervals (95% CI) were estimated for the associations between the metabolic conditions and AFB1 ‐albumin adduct levels categorized into quartiles. Results: The study found a significant association between AFB1 ‐albumin adduct levels and diabetes (Q4 vs Q1 POR = 3.74, 95%CI: 1.71‐8.19; P‐trend .003). No associations were observed between AFB1 ‐albumin adduct levels and the other conditions. Conclusions: As diabetes is the metabolic condition most consistently linked to HCC, the possible association between AFB1 exposure and diabetes may be of public health importance. Further studies are warranted to replicate the findings and examine potential mechanisms.